El fantástico de Narciso Ibáñez Serrador - Cordero Domínguez, Aída (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
The viewers have been fascinated by the fantastic since the first years of the cinema. In Spain the fantastic hasn’t had a constant evolution, nevertheless a group of film makers achieved for a short but intense period of time, known as “Golden Age”, the international recognition for Spanish fantastic cinema. One of these film makers is Narciso Ibáñez Serrador, who contributed with two horror movies: La Residencia (1969) and ¿Quién puede matar a un niño? (1976)